Engineered repairs of composite structures - Heslehurst, Rikard Benton (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
Engineered Repairs of Composite Structures provides a detailed discussion, analysis, and procedures for effective and efficient repair design of advanced composite structures. It discusses the identification of damage types and the effect on structural integrity in composite structures, leading to the design of a repair scheme that focusses on the restoration of the structural integrity and damage tolerance. This book teaches the reader to better understand effective and efficient repair design, allowing for more structurally effective repairs of damaged composite structures. It also discusses the application of the repair and what is needed in the forming of the composite repair to meet the engineering design requirements. Aimed at materials engineers, mechanical engineers, aerospace engineers, and civil engineers, this practical work is a must have for any industry professional working with composite structures.
Facing (Skin) Damage (Semi-Structural or Structural Repair)Facing (Skin) and Core Damage (Cosmetic); Facing (Skin) and Core Damage (Semi-Structural); Facing (Skin) and Core Damage-Structural Repair; Chapter 6: Composite Joining Methods and Design Requirements; Introduction; Bonded vs. Bolted Joints; Advantages and Disadvantages; Material Properties; Parent Structure and Repair Patch; Adhesive Properties; Fastener Properties; Composite Joint Design Hints; Adhesively Bonded Joints; Adhesive Characteristics; Adhesively Bonded Joint Failure Modes; Adhesively Bonded Double-Lap Joint
OCLC-licensed vendor bibliographic record.
Keywords: Concrete construction -- Maintenance and repair; Buildings, Reinforced concrete -- Maintenance and repair; TECHNOLOGY & ENGINEERING / Civil / General